(Chemical Composition of Indonesian Traditional Food Additives Which Possibly Containing Borax) - Atih Surjati Herman; Renawati Iskandar; Binarti Dwi Astuti (Balai Besar Industri Agro, 1991)
Five types of traditional food additives collacted from markets in Java and Manado, namely